Filiação socioafetiva e multiparentalidade : efeitos jurídicos quanto ao direito de guarda e ao direito de visitas - Beraldo, Maria Clara Bomtempo (2020)
Family precedes the State and the laws, in addition to representing the individual's first social contact, which makes its legal support so important. In Brazil, the content of Family Law has been changed and reinterpreted numerous times during the last decades, to adapt to social dynamics. In addition to the new infraconstitutional laws that appeared to modify or add to the Civil Code, the Federal Constitution of 1988 provided new reflections and new understandings on family relationships, based on fundamental rights. This context of changes in family law, then, allowed new family arrangements to be legally recognized, of which this dissertation aimed to analyze the recognition of socio-affective affiliation and multiparent families. As it deals with relatively new issues for doctrine and jurisprudence, there is a need to explore the means of guaranteeing the legal and social protection of the consequences generated by them. Countless are the legal effects produced by the formation of a family entity, of which the present study selected to deepen the exercise of custody and visits between parental figures and their children. To this end, this study was divided into four sessions, each focusing on a relevant aspect of the theme. Initially, the historical evolution of kinship relationships and the concept of family was analyzed so that it was possible to understand the way in which these relationships are treated, currently, in the Brazilian legal system. The influences that fundamental rights had on Family Law were also investigated. Then, the arguments that justify the recognition of socio-affective affiliation and multi parenting were demonstrated, as well as showing some possibilities in which they were admitted in the jurisprudence. Before entering the legal effects, it was necessary to understand the concept and applications of custody and visitation rights in Brazilian Family Law. Finally, the problem proposed in this research was verified, which is the triggering of the declaration of socio-affective affiliation and multiparenting, in order to understand how the legislation will need to adapt to the recognition of these new family entities, which still have not been properly regulated in Brazilian legislation on other areas of law, with a focus on the custody and visits institute. To this end, concrete cases were examined in which custody and visits have already occurred in these family arrangements in Brazilian jurisprudence, in addition to comparing the criteria and the foundations used in these decisions with those already provided for in the national legal system. Through bibliographical and documentary research, using the hypothetical-deductive method, then, it was assumed that the legal effects of the new family arrangements are not included in the infra constitutional legislation, but the in-depth analysis of the theme clarified that the means of application already consolidated in the legal system and custody, both for visits are also efficient when it comes to families whose bond originates from affection and when the family has a multiplicity of parental figures.